Teaching and discussing mental health among university students: a pilot arts-based study. Issue 1 (24th November 2020) - Atayero, Sarah; Dunton, Kate; Mattock, Sasha; Gore, Amanda; Douglas, Sarah; Leman, Patrick; Zunszain, Patricia
Abstract : Purpose: Interdisciplinary approaches to health education are becoming increasingly common. Here, the authors describe an arts-based approach designed by academics and artists to both supplement the study of mental illness and support the individual mental health of undergraduate and postgraduate university students, by raising the visibility of mental illness in an innovative way. Design/methodology/approach: Through workshops, university students were guided in a sensory and physical way to discuss psychological health and vulnerability. This was followed by the creation of physical representations of mental distress through art pieces. Findings: Students were able to design their own art pieces and discuss mental health issues in an open and creative way. Students reported that the arts-based initiative was beneficial to their practice as future professionals and provided a holistic learning experience. At the same time, artists were able to generate powerful images which facilitated further discussions within the faculty. Practical implications: This project provides an innovative model for workshops which could be employed to raise the visibility of common mental health disorders among university students while providing a safe space to discuss and support wellbeing. Additionally, variations could be implemented to enhance the teaching of affective disorders within a university curriculum. Originality/value: This paper presents the results of collaboration between academics and artists, who together generated an innovative way to both support students' mental health and provide an alternative way to supplement experiential learning about common mental health conditions such as anxiety and depression.